(3RGO GdeSjQ aj YdGL GdHhGSjQs - (3GdbhUhfj , TeS GdOjf eMeO Hf eMeO Hf eMeO Hf HOQ GdOjf GdbhUhfj,J (B931 (3g` s
(3ChdgG (B:s
(3hHYO (B: (3agPg QSGdI dWjag , eMJhjg Ydi eHGMK TQjag JJYdb HGdYdI GdeYQhaI HGdHhGSjQ s
(3BNQgG (B:s
(3hGdfaY ai GdehGO GdefLdHI Edjg hgPG eG GQOfG EjQGOg ai gPg GdQSGdI s
(3Cdag HQSe GdMGce GdTQYi HEbdje GdefhajI ef GdbWQ GdeUQis
(3hQJHg Ydi CQHYI aUhd hNGJeIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B7 - (3U (B56 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B11 - (3U (B260s
(3EjVGM Gdecfhf ddHZOGOi(B: (3L (B1 - (3U (B607 ; (3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA GdWH (B- (3bSe GdcJGH GdChd (B- (3U (B98 s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdWHs